Edukasi Orangtua terhadap Penurunan Spastisitas pada Anak Cerebral Palsy di Forum Buah Hati Colomadu Karanganyar - Sukadarwanto; Putri, Nitaya (Journal Of Human And Education (JAHE), 2024)
Cerebral palsy is a permanent and non-progressive brain damage characterized by hyperreflexia, abnormal movement patterns, weakness, abnormal tone (spasticity) and loss of ability of all four limbs where the legs are heavier than the arms. The muscle that often experiences spasticity is the gastrocnemius muscle which causes the ankle to be in a plantar flexion position and results in difficulty maintaining a standing position. Parents play a major role in controlling the level of spasticity in children, because most of the time the child is with their parents, so it is important to do additional knowledge in managing spasticity in order to support the functional abilities of children with cerebral palsy. The method of providing material is done through presented and feedback discussions, the implementation of educational programs containing pre-test quizzes, delivery of material using leaflet media, question and answer session discussions, post-test quizzes and feedback evaluation.